Dietary Supplements and Sports Performance: Minerals - Williams Melvin H (Taylor & Francis Group, 2005)
Abstract Minerals are essential for a wide variety of metabolic and physiologic processes in the human body. Some of the physiologic roles of minerals important to athletes are their involvement in: muscle contraction, normal hearth rhythm, nerve impulse conduction, oxygen transport, oxidative phosphorylation, enzyme activation, immune functions, antioxidant activity, bone health, and acid-base balance of the blood. The two major classes of minerals are the macrominerals and the trace elements. The scope of this article will focus on the ergogenic theory and the efficacy of such mineral supplementation.